If X - Y -Z AND l(XZ)=3√7,l(XY)=√7 THEN FIND
l(YZ)
Answers
Answered by
206
Step-by-step explanation:
l(XZ)=l(XY)+l(YZ)
3√7=√7+l(YZ)
l(YZ)=3√7-√7
=√7(3-1)
=√7(2)
l(YZ)=2√7
Answered by
8
Step-by-step explanation:
Given, and
Here, we see that
- Here, we have transposed constants to the right hand side and
to the left hand side.
Note:
- For the given picture, we must understand that
,
and
are collinear.
- If not collinear, we cannot write:
- However, here,
means
.
Attachments:
![](https://hi-static.z-dn.net/files/d98/aff9a04aaa44587a3d2742f205c5ba00.jpg)
Similar questions